Can exercise suppress tumour growth in advanced prostate cancer patients with sclerotic bone metastases? A randomised, controlled study protocol examining feasibility, safety and efficacy. Issue 5 (30th May 2017) - Hart, Nicolas H; Newton, Robert U; Spry, Nigel A; Taaffe, Dennis R; Chambers, Suzanne K; Feeney, Kynan T; Joseph, David J; Redfern, Andrew D; Ferguson, Tom; Galvão, Daniel A
Abstract : Introduction: Exercise may positively alter tumour biology through numerous modulatory and regulatory mechanisms in response to a variety of modes and dosages, evidenced in preclinical models to date. Specifically, localised and systemic biochemical alterations produced during and following exercise may suppress tumour formation, growth and distribution by virtue of altered epigenetics and endocrine–paracrine activity. Given the impressive ability of targeted mechanical loading to interfere with metastasis-driven tumour formation in human osteolytic tumour cells, it is of equal interest to determine whether a similar effect is observed in sclerotic tumour cells. The study aims to (1) establish the feasibility and safety of a combined modular multimodal exercise programme with spinal isometric training in advanced prostate cancer patients with sclerotic bone metastases and (2) examine whether targeted and supervised exercise can suppress sclerotic tumour growth and activity in spinal metastases in humans. Methods and analysis: A single-blinded, two-armed, randomised, controlled and explorative phase I clinical trial combining spinal isometric training with a modular multimodal exercise programme in 40 men with advanced prostate cancer and stable sclerotic spinal metastases. Participants will be randomly assigned to (1) the exercise intervention or (2) usual medical care. The intervention arm will receive a 3-month, supervised and individually tailored modular multimodal exercise programme with spinal isometric training. Primary endpoints (feasibility and safety) and secondary endpoints (tumour morphology; biomarker activity; anthropometry; musculoskeletal health; adiposity; physical function; quality of life; anxiety; distress; fatigue; insomnia; physical activity levels) will be measured at baseline and following the intervention. Statistical analyses will include descriptive characteristics, t-tests, effect sizes and two-way (group × time) repeated-measures analysis of variance (or analysis of covariance) to examine differences between groups over time. The data-set will be primarily examined using an intention-to-treat approach with multiple imputations, followed by a secondary sensitivity analysis to ensure data robustness using a complete cases approach. Ethics and dissemination: Ethics approval was obtained from the Human Research Ethics Committee (HREC) of Edith Cowan University and the Sir Charles Gairdner and Osborne Park Health Care Group. If proven to be feasible and safe, this study will form the basis of future phase II and III trials in human patients with advanced cancer. To reach a maximum number of clinicians, practitioners, patients and scientists, outcomes will be disseminated through national and international clinical, conference and patient presentations, as well as publication in high-impact, peer-reviewed academic journals. Trial registration number: ACTRN 12616000179437.